Students' mathematical reasoning ability in solving post-Covid-19 PISA model math problems - Linda Linda; Ira Asyura (Program Studi Pendidikan Matematika Program Pascasarjan Universitas Negeri Yogyakarta, 2021)
This study aims to describe the reasoning abilities of high school students in Pandeglang Regency, Indonesia in solving post-Covid-19 PISA model math problems. The subjects of this study were 80 students of two state senior high schools in Pandeglang Regency, Indonesia. The data collection used a written test consisting of four description questions in the form of PISA model math questions (levels 2, 3, 4, and 5), and were through interviews and documentation. The data analysis followed the steps of data reduction, data presentation, and conclusion drawing. The results show that the reasoning abilities of Pandeglang Regency high school students in post-Covid-19 are fair in following the rules of inference, checking the validity of arguments, proving, drawing logical conclusions, using patterns, analyzing mathematical situations, and generalizing. However, the reasoning abilities were very poor in providing explanations of models, facts, characteristics, and relationships; constructing valid arguments; and studying conjectures. Thus, it can be concluded that the mathematical reasoning ability of Pandeglang Regency senior high school students is poor when measured using the PISA Post-Covid-19 model of mathematics questions.